Timorese general secondary mathematics curriculum: Students’ perspectives on its implementation - Lucas, Margarida (2017)
In the aftermath of the 2002 Independence, Timorese education planning focused on the challenges of rebuilding schools, changing from an Indonesian curriculum into a new one, which required changing the language of instruction to Portuguese, and recruiting skilled teachers. A new curriculum for general secondary education (GSE) was implemented in 2012, which involved the development of didactic resources and teacher training - key elements in curriculum implementation. This paper presents partial results and focuses on students' perspectives regarding the implementation of the new Mathematics curriculum. Ninety-nine students from nine GSE schools participated in focus group discussions. Content analysis was used to analyse data pertaining to school conditions and infrastructures, textbooks and teachers' competences. Results showed that schools are ill-equipped, underfunded and lack (basic/manipulative) learning materials. The shortage of qualified teachers often resulted in inadequate service distribution and non-compliance with the number of weekly hours allocated to mathematics. Textbooks are clear and well organised, but language used demands a proficiency in Portuguese most students do not have, and they generally do not detail the resolution of tasks proposed. Teachers lack linguistic competences and continue to rely on textbooks from the Indonesian curriculum.